2021
DOI: 10.1371/journal.pone.0257945
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing in America: Understanding long-term adherence to COVID-19 mitigation recommendations

Abstract: A crucial question in the governance of infectious disease outbreaks is how to ensure that people continue to adhere to mitigation measures for the longer duration. The present paper examines this question by means of a set of cross-sectional studies conducted in the United States during the COVID-19 pandemic, in May, June, and July of 2020. Using stratified samples that mimic the demographic characteristics of the U.S. population, it seeks to understand to what extent Americans continued to adhere to social d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 86 publications
(94 reference statements)
5
31
0
1
Order By: Relevance
“…This is partly explained by the fact that women had a higher baseline adherence than men. Some studies have also reported the higher adherence to physical distancing of women in the pandemic first year [ 24 , 30 , 31 ]. However, the higher initial adherence of women led to a more pronounced relaxation until reaching a similar adherence to this measure in 2021 than men.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly explained by the fact that women had a higher baseline adherence than men. Some studies have also reported the higher adherence to physical distancing of women in the pandemic first year [ 24 , 30 , 31 ]. However, the higher initial adherence of women led to a more pronounced relaxation until reaching a similar adherence to this measure in 2021 than men.…”
Section: Discussionmentioning
confidence: 99%
“…As a likely result of intermittent prohibitions against evening dine-in services in Hong Kong restaurants since July 2020 [ 28 , 29 , 30 ], the use of food delivery/take out services greatly increased between the two study periods. Restaurant delivery services, which were rare in Hong Kong due to the close proximity of eating establishments to residential areas, quickly became available using mobile applications during this COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies conducted in the U.S., Europe and Africa had observed a gradual decline in adherence to COVID-19 preventive measures as the pandemic evolved [ 26 , 27 , 28 , 29 ]. However, other studies have noted that adherence to hygiene measures and social distancing recommendations have remained high during this pandemic [ 30 , 31 ] and that the intention to adhere to protective measures was also high [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that empirical network models can provide insight into the interplay of psychological factors that are important in relation to COVID-19-related behavior (Chambon et al, 2021 , 2022 ; Taylor et al, 2020 ). Furthermore, it represents a setting in which core variables from all five major compliance theories have been hypothesized to be at play (for a review, see Kooistra & van Rooij, 2020 ; also see Reinders Folmer et al, 2021 ). These features make this a setting that is ideally suited for understanding how these variables may interrelate with individual compliance in a complex network.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we expect that compliance with mitigation measures will be lower among more impulsive people, and among people who experience more negative emotions as a result of the pandemic. More generally, capacity theories thus imply that people will comply more with mitigation measures the more they are able to do so (Reinders Folmer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%